Genetic and morphometric rediscovery of an extinct land snail on oceanic islands. (14th February 2018) - Hirano, Takahiro; Wada, Shinichiro; Mori, Hideaki; Uchida, Shota; Saito, Takumi; Chiba, Satoshi
Abstract: Confirming the extinction of species with only old occurrence records is often difficult, due to the scarcity of biological information. Phylogenetic position and taxonomic status of the potentially extinct species are unclear in most such cases. In the present study, we document that a species of the endemic genus Hirasea of the oceanic Ogasawara Islands, which was formerly believed to have become extinct, still survives, on the basis of combined surveys involving molecular phylogenetics and morphometrics. Hirasea is notorious for its highly diversified shell morphologies and a number of species and subspecies have already become extinct because of environmental changes and impacts of alien predators. In this study, we first reconstruct phylogenetic relationships among extant Hirasea populations. Next, on the basis of quantitative shell morphological analysis of extant populations and type specimens, we identify morphological traits that reflect phylogenetic relationships among the species. By using these morphological traits and molecular phylogenies, we demonstrate that H. nesiotica liobasis, previously considered extinct, is still extant on Chichijima. Although classifications by means of morphology and molecular phylogeny often show incongruences, judgement of the conspecific status of living and extinct populations is still possible by considering ranges of variation and phylogenetic constraints on morphological traits.